Isolation and Identification of β-Sitosterol and Stigmasterol Mixture from Root Bark of Slatri (Calophyllum soulattri Burm. f) - Doni Eko Saputra; Nestri Handayani; Muhammad Widyo Wartono (UNIVERSITAS SEBELAS MARET (UNS), 2018)
Chemical isolation and identificationof root bark of CalophyllumsoulattriBurm. f. have been conducted. Isolation was conducted by maceration with ethyl acetate as solvent. Ethyl acetate extract was separated and purified by vacuum liquid chromatography and flash chromatography which was guided by thin layer chromatography to obtain yellowish white solid. Isolated compounds were determined by spectroscopy methods such as UV, FTIR, 1H NMR, 13C NMR, DEPT, HSQC, HMBC and were compared to the references. Based on the analysis result it’s known that the compounds are the mixture of?-sitosterol and stigmasterol.